2019
DOI: 10.1017/s000711451900326x
|View full text |Cite
|
Sign up to set email alerts
|

Higher intakes of dietary vitamin D, calcium and dairy products are inversely associated with the risk of colorectal cancer: a case–control study in China

Abstract: The effects of dietary vitamin D, Ca and dairy products intakes on colorectal cancer risk remain controversial. The present study investigated the association between these dietary intakes and the risk of colorectal cancer in Guangdong, China. From July 2010 to December 2018, 2380 patients with colorectal cancer and 2389 sex- and age-matched controls were recruited. Dietary intake data were collected through face-to-face interviews using a validated FFQ. Unconditional multivariable logistic regression models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 52 publications
4
16
0
Order By: Relevance
“…Dietary branched-chain amino acids and cancer effect modification was observed in the model including dairy products, whose consumption is partially correlated with Ca intake. Only the adjustment for fish consumption and vitamin D slightly increased the OR estimates (0•82 and 0•87 for the highest v. the lowest quintile of BCAA intake, respectively), suggesting a possible role of vitamin D, in addition to Ca, in explaining the observed associations with CRC, in line with the literature (23)(24)(25)(26) . In an additional model, including both dietary Ca and vitamin D, no association with BCAA was evident.…”
Section: Discussionsupporting
confidence: 82%
“…Dietary branched-chain amino acids and cancer effect modification was observed in the model including dairy products, whose consumption is partially correlated with Ca intake. Only the adjustment for fish consumption and vitamin D slightly increased the OR estimates (0•82 and 0•87 for the highest v. the lowest quintile of BCAA intake, respectively), suggesting a possible role of vitamin D, in addition to Ca, in explaining the observed associations with CRC, in line with the literature (23)(24)(25)(26) . In an additional model, including both dietary Ca and vitamin D, no association with BCAA was evident.…”
Section: Discussionsupporting
confidence: 82%
“…Several epidemiological studies, meta-analyses, and supplemental studies have tried to determine the specific role of circulating, dietary, and/or supplemental vitamin B12 with CRC risk, although the results are still controversial. For example, two meta-analyses of prospective and case-control studies and a case-control study evaluated the association between circulating and vitamin B12 intake and CRC risk, which concluded that dietary vitamin B12 was inversely associated with the risk of CRC [23][24][25]. However, other studies did not find significant associations between CRC risk and neither dietary [26] nor serum vitamin B12 [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies from Korea [6], Japan [16], China [17] and two women cohorts from the European Prospective Investigation into Cancer and Nutrition (EPIC) study [18] also reached the same conclusion, while other studies [19][20][21][22] have shown no association between colorectal cancer risk and high dietary calcium intake. The variance in these findings is likely due to differences in intake of calcium-based foods resulting from differences in food cultures.…”
Section: Discussionmentioning
confidence: 61%